Sigmoid Generalized Complementary Equation for Evaporation Over Wet Surfaces: A Nonlinear Modification of the Priestley‐Taylor Equation. Issue 9 (31st August 2021) - Han, Songjun; Tian, Fuqiang; Wang, Wei; Wang, Liming
Abstract: The deviations of the Priestley‐Taylor (PT) coefficient from a fixed value around 1.26 indicate a nonlinear dependence of wet surface evaporation ( E ) on the equilibrium evaporation ( E rad, which is the radiation term in Penman potential evaporation [ E Pen ]). The linear PT equation with a fixed coefficient underestimates E for small E rad but overestimates E for large E rad, whereas the Penman equation with calibrated linear wind function has the opposite bias. In this study, the sigmoid generalized complementary (SGC) equation by Han and Tian (2018a), https://doi.org/10.1029/2017wr021755 was applied to estimate the wet surface evaporation by setting its asymmetric parameter to infinity. The SGC equation with one fixed parameter captures the nonlinear dependence of E on E rad over wet surfaces by including the aerodynamic component of E Pen with a reference wind function, and amends the shortages of the linear PT and Penman equation. By using datasets over open water surfaces of lakes and ocean, wetlands, and paddy fields, the validation results indicate that the wet surface SGC equation performed better than the linear PT and Penman equations on evaporation estimation. The success of the wet surface SGC equation has implications for the extension of the complementary principle to consider varying aerodynamic conditions over wet surfaces. Key Points: Sigmoid generalized complementary (SGC) equation is applied to wet surfaces Wet surface SGC equation outperforms the linear Priestley‐Taylor (PT) equation because it considers the varying PT coefficient Complementary principle can be extended to consider varying aerodynamic conditions over wet surfaces